Epidemiology of chronic multimorbidity and temporary migration in a rural South African community in health transition: A cross-sectional population-based analysis - Dzomba, Armstrong; Ginsburg, Carren; Kabudula, Chodziwadziwa W.; Yorlets, Rachel R.; Ndagurwa, Pedzisai; Harawa, Sadson; Lurie, Mark N.; McGarvey, Stephen T.; Tollman, Stephen; Collinson, Mark A.; White, Michael J.; Gomez-Olive, Francesc X. (Frontiers in Epidemiology, 2023)
In sub-Saharan African settings, the increasing non-communicable disease mortality is linked to migration, which disproportionately exposes sub-populations to risk factors for co-occurring HIV and NCDs. We examined the prevalence, patterns, and factors associated with two or more concurrent diagnoses of chronic diseases (i.e., multimorbidity) among temporary within-country migrants. Employing a cross-sectional design, our study sample comprised 2144 residents and non-residents 18-40 years interviewed and with measured biomarkers in 2018 in Wave 1 of the Migrant Health Follow-up Study (MHFUS), drawn from the Agincourt Health and Demographic Surveillance System (AHDSS) in rural north-eastern South Africa. We used modified Poisson regression models to estimate the association between migration status and prevalent chronic multimorbidity conditional on age, sex, education, and healthcare utilisation. Overall, 301 participants (14%; 95% CI 12.6 – 15.6), median age 31 years had chronic multimorbidity. Multimorbidity was more prevalent among non-migrants (14.6%; 95% CI 12.8 – 16.4) compared to migrants (12.8%; 95% CI 10.3 – 15.7). Non-migrants also had the greatest burden of dual-overlapping chronic morbidities, such as HIV-obesity 5.7%. Multimorbidity was 2.6 times as prevalent (PR 2.65. 95% CI 2.07 – 3.39) among women compared to men. Among migrants, men and individuals with secondary or tertiary education manifested lower prevalence of two or more conditions. In a rural community with colliding epidemics, we found low but significant multimorbidity driven by a trio of conditions: HIV, hypertension, and obesity. Understanding the multimorbidity burden associated with early adulthood exposures, including potential protective factors (i.e., migration coupled with education), is a critical first step towards improving secondary and tertiary prevention for chronic disease among highly mobile marginalised sub-populations.